Want this question answered?
Be notified when an answer is posted
Wow you really can't spell.
The nth term of the sequence is 3n-8 and so the 30th term is 3*30 -8 = 82
There are not enough numbers to be certain. The rule for the nth term could be Subtract 6 from the previous term giving 30, 24, 18, etc or Multiply previous term by 0.8 giving 30, 24, 21.6, etc etc
23 and 53
The next number is 30+7 = 37.
The nth term is 7n-5 and so the 6th term will be 37
6n+10
9 ,16 ,23, 30 We note that there is a difference of '7' between terms. So the first part of the 'nth' term is 7n. Note the '7' becomes multiple. Next we need to find the constant 'c' So taking the first term (n = 1) we write. 7n + c = 9 7(1) + c = 9 7 + c = 9 c = 2 So the 'nth' term is '7n + 2' To verify , try the 3rd term n= 3 then answer should be '23'. 7(3) + 2 = 21 + 2 = 23 As required.
t(n) = 5 - 7n for n = 1, 2, 3, ... The difference between each term is -7, therefore the nth term will be: t(n) = -2 + -7 × (n - 1) = -2 + 7n + 7 = 5 - 7n
We note that the numbers rise by addition of ;7;7 between terms. Hence we can write 7n . The first term( n- 1) is '9' So we can write 7(1) + c = 9 7 + c = 9 c = 2 So the nth term becomes 7n + 2
Clearly here the nth term isn't n25.
90
To find the nth term of a sequence, we first need to identify the pattern or rule governing the sequence. In this case, the sequence appears to be increasing by consecutive odd numbers: 10, 14, 18, 22, and so on. To find the nth term, we can use the formula for the nth term of an arithmetic sequence: a_n = a_1 + (n-1)d, where a_n is the nth term, a_1 is the first term, n is the position of the term, and d is the common difference. In this sequence, a_1 = 6 and the common difference is 10. Therefore, the nth term can be expressed as a_n = 6 + (n-1)10.
Well, honey, if the nth term is 3n-1, then all you gotta do is plug in n=30 and do the math. So, the 30th term would be 3(30)-1, which equals 89. There you have it, sweet cheeks, the 30th term of that sequence is 89.
30
Just plug in 30 for n in 3n-1. The answer is 89.
3 x 10(n-1)